2015
DOI: 10.23917/forgeo.v29i1.786
|View full text |Cite
|
Sign up to set email alerts
|

Application of Vector Auto Regression Model for Rainfall-River Discharge Analysis

Abstract: River discharge quantity is highly depended on rainfall and initial condition of river discharge; hence, the river discharge has auto-correlation relationships. This study used Vector Auto Regression (VAR) model for analysing the relationship between rainfall and river discharge variables. VAR model was selected by considering the nature of the relationship between rainfall and river discharge as well as the types of rainfall and discharge data, which are in form of time series data. This research was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…As the comparison, previous study conducted by Gebreyohannes et al (2014) found the result of regression analysis between daily rainfall and peak discharge, in which the coefficient of determination was 0.50-0.94 with confidence interval of 99% in 11 observed catchments. In addition, Hartini et al (2015) applied vector autoregression on rainfall and discharge at Sojomerto, Juwero, and Glapan, which obtained the relationship between those variables of 6.4%-70%. 4.…”
Section: Results and Discussion A Land Cover Of The Study Areamentioning
confidence: 99%
“…As the comparison, previous study conducted by Gebreyohannes et al (2014) found the result of regression analysis between daily rainfall and peak discharge, in which the coefficient of determination was 0.50-0.94 with confidence interval of 99% in 11 observed catchments. In addition, Hartini et al (2015) applied vector autoregression on rainfall and discharge at Sojomerto, Juwero, and Glapan, which obtained the relationship between those variables of 6.4%-70%. 4.…”
Section: Results and Discussion A Land Cover Of The Study Areamentioning
confidence: 99%
“…Yoke et al [29] found the VAR model suitable for modeling rainfall and ground level; a one-way causality between rainfall and groundwater level is reported using the Granger causality. Hartini et al [30] discussed the significant relationships between river discharge and rainfall, indicating that the study area moved downstream.…”
Section: Related Workmentioning
confidence: 97%
“…Distance from the river is one of the main causative factors due to its significant impact on the spread and magnitude of flooding that will occur [30]. Areas close to rivers are more prone to flooding within the watershed due to water flowing from higher elevations and accumulating at lower elevations, where mostly when it rains, areas close to terrestrial water bodies become flooded, such as rivers, swamps, ponds, and lakes [31].…”
Section: Parametermentioning
confidence: 99%